Families with neurodevelopmental diagnoses are not ‘Hard to Reach’: Findings from a feasibility trial comparing parenting programmes for parents of children with ADHD - Fiona Sim; Lindsay Dalgarno; Emma McIntosh; Caroline Haig; Patrycja Duklas; Alex McConnachie; Christopher Gillberg; Helen Minnis; Lucy Thompson (PLoS ONE, 2025)
Attention-Deficit/Hyperactivity Disorder (ADHD) is defined by impairing levels of inattention and/or hyperactivity-impulsivity. It occurs in at least 5% of school age children and 2.5% of adults worldwide, and is associated with multiple negative outcomes throughout life. There is good evidence to support the efficacy of pharmacological treatment of individuals affected, and also of behavioural training for parents of children with ADHD, though the optimal focus and format to support change has yet to be established. This feasibility, parallel-group, randomised, controlled, pilot trial examined the feasibility of comparing two parenting programmes for families of school-aged children with ADHD. Parents of children aged 5–12 years with a clinical diagnosis of ADHD, referred to a regional integrated ADHD pathway, were randomly allocated (1:1 in permuted blocks of 4) either to a Parents InC or Incredible Years (IY) parenting group. The primary feasibility outcomes were recruitment and retention rates. The putative primary effectiveness outcome measure was Parenting Sense of Competence Scale (PSOC) and secondary outcome measures included the behavioural, physical, and emotional functioning of the child as well as health and ADHD symptoms of the parents at 12 (or 6 in final four participants) months post-randomisation. Process and economic evaluations were also included. We recruited 30/52 (58%) eligible participants (14 randomised to Parents InC, 16 to IY). Twenty-two participants (73%) provided follow-up quantitative data and 24 (80%) participated in qualitative interviews. PSOC scores were suggestive of greater improvement in Parents InC groups than IY groups. Power calculations suggest we will need to recruit 230 participants for a definitive RCT. Health economic analysis showed Parents InC had a lower per-group costs. Participant feedback on research procedures and methods was positive, and interviews and process evaluation provided a rich source of learning points to take forward into a future trial. Trial registration Clinical Trials, protocol registration system: NCT03832270.